Alternative Performance Measures: Determinants of Disclosure Quality – Evidence from Germany. (2nd January 2021) - Jana, Stephanie; McMeeking, Kevin
ABSTRACT: Alternative performance measures (APMs) might be used to improve the information environment or strategically to mislead the market. The recently introduced European Securities and Markets Authority APM guidelines are intended to enhance corporate financial disclosures. We analyse the disclosure quality and determinants of all types of APMs in management reports of German listed firms for two financial periods. Although the quantity of APM disclosures is extensive, it differs across firms' characteristics, and there is considerable room for improvement regarding disclosure quality. APM disclosure quality is positively associated with firm size and negatively associated with profitability. However, not all firms' characteristics can be applied per se as universal determinants of APM disclosure quality, and a distinction must be made between different types of APMs. For example, high ownership concentration is negatively associated particularly with the quality of profitability APMs. Firms' leverage is positively associated with the disclosure quality of non-profitability APMs.